Impact of Supply Chain Integration on Competitive Advantage - Sinaga, Obsatar; Riantani, Suskim; Hendayana, Yana; Saudi, Mohd Haizam Mohd; Zainudin, Zalina (ExcelingTech, 2019)
The interaction of supply chain management with other disciplines such as knowledge management is gaining increasing attention as their synergic relation is becoming an important competitive tool. Therefore, the current study is carried out to examine the relationship, between supply chain integration, knowledge management and competitive advantage. We have used the smart PLS as statistical tool to achieve the research objectives the data by mean of an adapted survey instrument in the form of questionnaire is collected from the operation and finance managers of Indonesian manufacturing firms. The results of the current study are providing support to the hypothesized results. The direct and indirect relations appears positive and significant The current study which in author knowledge is among few pioneering studies on this issue, will be helpful for financial experts, operation managers, academicians, researchers and other policy makers in formulating policies.